2015
DOI: 10.18632/oncotarget.6200
|View full text |Cite
|
Sign up to set email alerts
|

Can active components of licorice, glycyrrhizin and glycyrrhetinic acid, lick rheumatoid arthritis?

Abstract: OBJECTIVESThis review stated the possible application of the active components of licorice, glycyrrhizin (GL) and glycyrrhetinic acid (GA), in rheumatoid arthritis (RA) treatment based on the cyclooxygenase (COX)-2/thromboxane A2 (TxA2) pathway.METHODSThe extensive literature from inception to July 2015 was searched in PubMed central, and relevant reports were identified according to the purpose of this study.RESULTSThe active components of licorice GL and GA exert the potential anti-inflammatory effects throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 61 publications
1
18
0
Order By: Relevance
“…In reflection of the frequent clinical application of these herbs in combination with conventional medications, some studies have examined combined effects. For example, compounds from Glycyrrhiza uralensis Fisch have been reported to enhance the therapeutic effects of NSAIDs and DMARDs [68], and the compound ligustrazine derived from Ligusticum chuanxiong Hort. was reported to reduce bone cortex erosion when combined with leflunomide in a clinical study [99].…”
Section: Modern Research Into Herbs Used Frequently In Thementioning
confidence: 99%
See 1 more Smart Citation
“…In reflection of the frequent clinical application of these herbs in combination with conventional medications, some studies have examined combined effects. For example, compounds from Glycyrrhiza uralensis Fisch have been reported to enhance the therapeutic effects of NSAIDs and DMARDs [68], and the compound ligustrazine derived from Ligusticum chuanxiong Hort. was reported to reduce bone cortex erosion when combined with leflunomide in a clinical study [99].…”
Section: Modern Research Into Herbs Used Frequently In Thementioning
confidence: 99%
“…6 Evidence-Based Complementary and Alternative Medicine Liquiritin [66], glycyrol [67], glycyrrhizin, glycyrrhetinic acid [68] (i) Anti-inflammatory [66][67][68], (ii) restrained angiogenesis [66], (iii) down-regulated autoimmune reactions [67], (iv) enhanced therapeutic effects of NSAIDs/DMARDs [68] Jiang, Sheng jiang, Gan jiang…”
Section: Syndromes In 2018 Guidelinementioning
confidence: 99%
“…Some previous researches have shown that betulinic acid, kaempferol, leonurine, oxymatrine, and piperlongumine can inhibit the migration and invasion of FLS in RA models (Li et al, ; Liang et al, ; Liu, Feng, et al, ; Pan et al, ; Sun, Xu, Du, Zhang, & Zhu, ). Triptolide, celastrol, geniposide, paeoniflorin, clematichinenoside AR, glycyrrhetinic acid, kirenol, cucurbitacin E, 1,7‐dihydroxyl‐3,4‐dimethoxylxanthone, calycosin, catechin, cyanidin‐3‐glucoside, quercetin, α‐mangostin, leonurine, norisoboldine, oxymatrine, caffeic acid, paeonol, resveratrol, shikonin, and 3 R ‐(4′‐hydroxyl‐3′‐ O ‐β‐ d ‐glucopyranosyl phenyl)‐dihydro isocoumarin alleviate inflammatory response by inhibiting the release of a variety of proinflammatory factors (e.g., activin A, ciliary neurotrophic factor, and fractalkine) in FLS of RA models (Bi et al, ; Chen et al, ; Deng et al, ; Huang et al, ; Jia et al, ; Li et al, ; Liang et al, ; Lin, Sato, & Ito, ; Liu, Feng, et al, ; Mao, Sun, Pei, & Zhang, ; Su et al, ; Su et al, ; Sun et al, ; Sun et al, ; Sun & Li, ; Sung et al, ; Tang et al, ; Tian, Chen, Gao, Li, & Xie, ; Venkatesha, Astry, Nanjundaiah, Yu, & Moudgil, ; Wang, Sun, & Jin, ; Wei et al, ; Yang et al, ; Yang et al, ; Zhang et al, ; Zheng et al, ; Zuo et al, ).…”
Section: The Anti‐ra Activities Of Chemical Constituents From Herbal mentioning
confidence: 99%
“…Multiple inflammatory indices (e.g., TNF‐α, IL‐1, and IL‐6) are dysregulated in the peripheral blood of RA patients, which may also participate in the mechanisms of some constituents against RA, including triptolide; paeoniflorin; artesunate; artemether; glycyrrhizin; madecassoside; taraxasterol; apigenin; luteolin; quercetin; 1,7‐dihydroxyl‐xanthone; 2‐hydroxyl‐1,7‐dimethoxylxanthone; 1,7‐dihydroxyl‐3,4‐dimethoxylxanthone; berberine; norisoboldine; oxymatrine; sinomenine; curculigoside A; curcumin; ferulic acid; p‐coumaric acid; daphnetin; and matrine (Cai, Zheng, Shang, Zhao, & R., Y., ; Cuzzocrea, Saadat, Di Paola, & Mirshafiey, ; Ding et al, ; Gao, Shan, Di, Jiang, & Xu, ; Huang et al, ; Impellizzeri et al, ; Jia & He, ; Jiang, Ping, Sun, Wang, & Sun, ; Li et al, ; Lin et al, ; Luo et al, ; Ma et al, ; Pu et al, ; Shi, Zhou, Ji, Xu, & Yang, ; Tu, Hu, & Lu, ; Wang et al, ; Wang, Mo, & Zhang, ; Yang, Zhang, et al, ; Zhai et al, ; Zheng et al, ; Zhou, Wong, Wang, Cai, & Liu, ; Zhu et al, ; Zhu et al, ; Zuo, Xia, Li, & Chen, ). In addition, some kinds of cells in peripheral blood are also involved in the inflammatory processes of RA.…”
Section: The Anti‐ra Activities Of Chemical Constituents From Herbal mentioning
confidence: 99%
“…18β-Glycyrrhetinic acid (18b-GA) is a product of glycyrrhizin metabolism through the intestinal flora [11]. 18b-GA has recently been reported to have anti-inflammatory [12], anticancer [13,14], and hepatoprotective [15] effects. In addition, recent evidence indicates that 18b-GA exerts a powerful protective effect in multiple liver injury models, including models of exposure to free fatty acids [16], BA [9], a choline-deficient L-amino acid-defined diet [17], and carbon tetrachloride [18].…”
Section: Introductionmentioning
confidence: 99%